人工智能在国际中文教育课堂的应用研究现状及发展趋势 - Shuang Zhang; Yiting Liu; Wenlong Liu (Journal of Maobi, 2025)
The application of cutting-edge technologies such as artificial intelligence is profoundly influencing international Chinese education. Against this backdrop, deeply exploring the application of artificial intelligence in international Chinese education is of far-reaching significance for improving the quality of international Chinese education and promoting its entry into a new era of digitalization and intelligence. Following scoping review and based on CiteSpace, this study aims to determine the overall trend, research progress, and research hotspots on artificial intelligence in international Chinese educationin in CNKI in the past five years from 2021 to 2025 to accurately grasp the stage research dynamics and development trends. It has been found that 1) there is an incremental trend in artificial intelligence research in international Chinese education, and there is no close tie of cooperation among researchers and institutions in terms of this topic, with College of Chinese as a Foreign Language, East China Normal University, and School of Literature, Capital Normal University as the institutions that have the most publication number in this field; 2) a multiple hot spots were identified as follows: artificial intelligence and technological application, challenges and responses in transformation, systematic and professional construction; 3) the combination of artificial intelligence and international Chinese education has great potential for development.